Kansei Engineering dalam Perbandingan Desain Aplikasi Mobile Banking Himbara - Yayat Sutrayana (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze and evaluate the interface design of mobile banking applications at banks affiliated with HIMBARA (Association of State-Owned Banks) using the Kansei Engineering method, and to identify the most important design elements for users. The research method used is Kansei Engineering, which allows researchers to translate human feelings and perceptions into design specifications. This study involved 15 Kansei words relevant to user experience, and 4 different design specimens. Data were collected through a survey involving 55 HIMBARA bank customers as the population and research sample. Customer responses were analyzed using various multivariate statistical analysis techniques, including correlation coefficient analysis (CCA), principal components analysis (PCA), and factor analysis (FA). The results of the study indicate that certain emotional factors, such as a sense of "Safe" and "Easy to Use", are the interface design elements that most influence user satisfaction. Based on these results, this study provides design recommendations that consider the emotional and psychological aspects of users to improve the experience of using the HIMBARA Bank mobile banking application.